You assume a value of t that is increased over the t in the equations.

(I don't have to do that, but you have to, so that you will understand the solution)

Let us the t in the equations is t=1.

x = -5*1 -3 = -8

Then, we increase t, say t = 3,

x = -5*3 -3 = -18

So, the x decreases as t increases. -------**

Do that on the y.

Old y, when t = 1,

y = 5t +4

y = 5*1 +4 = 9

New y, when t = 3,

y = 5*3 +4 = 19

So, the y increases as the t increases. -----**

Therefore, 2) x decreases, and y increases. -----------answer.